Epidermólise bolhosa no Espírito Santo: caracterização sociodemográfica e avaliação de alterações na mucosa oral - Franzosi, Ana Carolina Sias Franco (2024)
Introduction: Epidermolysis Bullosa (EB) is a severe genetic disease characterized by continuous blistering of the skin and mucous membranes, potentially presenting significant structural changes in the mouth. Objective: To analyze the nuclear aspects of cytotoxicity and mutagenicity obtained from exfoliated cells of the buccal mucosa in EB patients. Materials and Methods: Sociodemographic and clinical information were collected through physical examination and a standardized questionnaire. Buccal mucosa cells were obtained from oral exfoliations and evaluated to determine the frequency of micronuclei, karyorrhexis, karyolysis, and pyknosis. The statistical tests used were Mann-Whitney and Kruskal-Wallis. Results: 20 EB individuals were selected, and the control group (n=20) was matched for sex and age with the EB sample. A similar distribution was observed between men (n=8, 40%) and women (n=12, 60%), and individuals aged ≥ 19 years represented the majority (n=13, 65%). Quantitative analysis revealed that most cells were identified as normal in both groups. A higher number of karyorrhexis (p=0.0002) and karyolysis (p<0.0001) was observed in the EB sample. Micronuclei were found only in the latter group. When comparing non-EB patients with the most severe cases of the disease, a higher number of karyolysis was identified in the EB sample (p=0.0006). Conclusion: Nuclear alterations of cytotoxicity were more frequent in the EB group. Mutagenicity-related changes were found only in this group. This reinforces the need for constant medical and dental follow-up to prevent the establishment of more severe conditions.